2018
DOI: 10.1029/2018gl079118
|View full text |Cite
|
Sign up to set email alerts
|

Juno Constraints on the Formation of Jupiter's Magnetospheric Cushion Region

Abstract: Observations by the Pioneer, Voyager, Ulysses, and Galileo spacecraft in Jupiter's dayside magnetosphere revealed a cushion region, where the magnetic field became increasingly dipolar and the 10-hr periodicity associated with rotation of the magnetodisc was no longer visible. Focused observations at the dawn terminator by the Juno spacecraft provide critical constraints on the formation physics of the dayside cushion. We observe a persistent 10-hr periodicity at dawn with only minor distortions of the field n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…This most likely means that during our observations, Jupiter is north of the solar current sheet more often than south of it (since the solar dipole is pointing northwards during this solar cycle). As mentioned by Gershman et al (2018), Juno's orbital period is close to double the solar rotation period. So from orbit to orbit, Juno will see similar solar wind conditions, like magnetic field direction, while in the magnetosheath.…”
Section: 1029/2019ja027382mentioning
confidence: 77%
“…This most likely means that during our observations, Jupiter is north of the solar current sheet more often than south of it (since the solar dipole is pointing northwards during this solar cycle). As mentioned by Gershman et al (2018), Juno's orbital period is close to double the solar rotation period. So from orbit to orbit, Juno will see similar solar wind conditions, like magnetic field direction, while in the magnetosheath.…”
Section: 1029/2019ja027382mentioning
confidence: 77%
“…Due to the flapping motion of the magnetodisk, Juno periodically crosses the equatorial plane (local B minimum) and reaches the plasma sheet edge (local B maximum). This plasma sheet edge (presumably the PSBL) is characterized by (1) weak thermal electron fluxes, (2) field‐aligned pitch‐angle distributions of high‐energy electrons, and (3) intense wave electric field bursts on top of the continuum radiation (tracking the density variations and indicating that Juno is on closed field lines; see, e.g., Hospodarsky et al., 2017; Gershman et al., 2018). In this study, we collect statistics of Juno observations during such crossings of the magnetodisk.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the return flow of depleted electrons at dawn found in this study may carry energetic plasma not observable by ELS. Further effort and investigations are required to make a more conclusive statement on this topic at Saturn (and it seems, also at Jupiter: Gershman et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This region also exhibits dipolar configurations of the magnetospheric field and magnetic nulls, which arise from instabilities that form at the outer edge of the plasma sheet. Most recently, there is evidence that the concept of the cushion region may need to be reassessed because the Juno spacecraft did not observe a persistent cushion region on the dawn flank (Gershman et al, 2018). Went et al (2011) compared observations from Jupiter (with the Ulysses spacecraft) and Saturn (Cassini) and concluded that Saturn lacked a cushion region of quasi-dipolar flux tubes.…”
Section: Equatorial Plane-lt Asymmetrymentioning
confidence: 99%